The Evaluation of The Professional Training Programs In Romanian Local Public Administration: A Quantitative Research - Corina-Cristiana NASTACA; Claudiu-Emanuel SIMION; Madalin-Valentin DRAGUT (Communications of International Proceedings, 2022)
The purpose of the article is to conduct an analysis at the level of local public administration in Romania on the evaluation and impact of training programs in which employees participated, between 2019 and 2022. The research method used was the opinion survey, conducted using a self-administered questionnaire, designed by the authors, based on the main studies in the field. The questionnaire was sent to 41 county councils, 216 municipalities and 103 town halls, obtaining 202 answers. The data obtained was processed using the statistical software SPSS 22.0. The results indicate a good general perception of the respondents regarding the training process, but there are certain aspects that can be improved, such as: increasing the frequency of participation in professional training programs, paying special attention to training in staff promotion, improving the practical component training and analysis of the entire administration on the evaluation and impact of training programs.
Keywords: professional training; public administration; satisfaction; assessment